PARALINGUISTIC TOOLS IN THE ENGLISH AND UZBEK LANGUAGE SYSTEM - L.N., , Umarova (International Journal of Psychosocial Rehabilitation, 2020)
In this article we will try to consider some methodological principles and features of teaching a foreign language in a technical university, based on the criteria for the development of professional competence. There is no doubt that establishing a good communication between students and the teacher introduces successful steps for both learning and teaching process. Communication is more than words, and it is important for teachers to understand the nonverbal messages they are sending and receiving in the classroom. Body language includes facial expressions, eye contact or lack of eye contact, proximity and closeness, hand gestures. Much of the research about nonverbal communication indicates that as little as 7 percent of communication is spoken words and the majority is nonverbal and paralinguistic ones